Chilling units and chilling hours for southern region of Brazil and Aomori in Japan - YOSHIKAWA, Eiji Reonardo; PETRI, José Luiz; SEZERINO, André Amarildo (Revista Teste SPGG, 2018)
The brazilian apple production are located in the southern region, with the best areas in altitudes ranging from 800 to 1400 m, with great variability in the number of Chilling Hours (CH) and Chilling Units (CU) in the different regions and years. The objective of this study was to compare CH equal or below 7.2°C and CU by the North Carolina Modified model in different regions of southern Brazil, comparing with Aomori region in Japan. In Brazil was used historical data of the CH and CU from 2000 to 2016 in the municipalities of Caçador (960 m), Videira (774 m), São Joaquim (1376 m), Fraiburgo (1038 m) and Vacaria (986 m). In Aomori (2.8 m) the historical data used was from 2000 to 2011. The results shows that in southern Brazil there is a variation in the number of CH between sites and years, being greater in the sites of higher altitude, with an average of 880 CH in São Joaquim and 411 CH in Videira. When compared the brazilian regions with Aomori, the japanese region have a greater CH accumulation. Once CU have the same behavior of CH in respect to altitudes, but shows a larger variability between years in the different regions of southern Brazil, is possible to affirm that the North Carolina Modified method is more accurate to quantify the chilling in regions with large temperature fluctuations in the autumn and winter, while for regions with low thermal amplitude, the model of CH presents a better adherence.